The Oxford handbook of early Christian apocrypha - Gregory, Andrew F. 1971-; Tuckett, Christopher M. 1948-; Nicklas, Tobias 1967-; Verheyden, Joseph 1957-; Oxford University Press (Oxford Oxford University Press, 2018)
The Oxford Handbook of Early Christian Apocrypha' addresses issues and themes that arise in the study of early Christian apocryphal literature. It discusses key texts including the Gospel of Thomas, the Gospel of Mary, the Gospel of Peter, letters attributed to Paul, Peter, and Jesus, and acts and apocalypses written about or attributed to different apostles. Part One consists of authoritative surveys of the main branches of apocryphal literature (gospels, acts, epistles, apocalypses, and related literature) and Part Two considers key issues that they raise. These include their contribution to our understanding of developing theological understandings of Jesus, the apostles and other important figures such as Mary. It also addresses the value of these texts as potential sources for knowledge of the historical Jesus, and for debates about Jewish-Christian relations, the practice of Christian worship, and developing understandings of asceticism, gender and sexuality, etc.0The volume also considers questions such as which ancient readers read early Christian apocrypha, their place in Christian spirituality, and their place in contemporary popular culture and contemporary theological discourse
Originally published: 2015
Keywords: Apocryphal books -- Criticism, interpretation, etc; Apocryphal books; Aufsatzsammlung